Acute small bowel obstruction caused by a fan-shaped congenital band in a child: a case report - Lan, Qingnan; Zhong, Jianhua; Wang, Yi; Zhu, Haiwei; Liu, Xin; Guo, Yanping; Qu, Zhibo (Frontiers in Pediatrics, 2025)
Congenital bands are rare abnormal structures that can occur anywhere in the gastrointestinal tract, and intestinal obstruction caused by these bands is uncommon in children. To our knowledge, there have been no reported cases of small bowel obstruction (SBO) resulting from a wide, fan-shaped congenital band located on the surface of the ileum and mesentery. We present the case of a 13-year-old girl who developed SBO due to a unique fan-shaped band that compressed a segment of the ileum. The diagnosis of intestinal obstruction was confirmed through x-ray and CT imaging, and the location and cause of the obstruction were further elucidated during exploratory laparotomy. The band was excised, with no bowel resections required. Congenital or spontaneous bands are rare causes of bowel obstruction, and accurately diagnosing this condition prior to surgery can be challenging. When considering the potential causes of intestinal obstruction, it is crucial to include congenital bands in the differential diagnosis.